Measuring lexical richness in the writings of esl learners at a tertiary institution in Malaysia / Roslina Abdul Aziz ...[et al.] - Abdul Aziz, Roslina; Supian, Suzaini Hamiruslin; Abdul Sukor, Fatin Sabrina; Nikman, Khairunisa (Universiti Teknologi MARA Cawangan Pahang, 2021)
This study aims at measuring the lexical richness of first semester students from Universiti Teknologi MARA Cawangan Pahang with the research objectives of measuring the use of 1000-, 2000-word level and AWL level in the writings and comparing the lexical profile in the writings of students from different disciplines. The study employed a quantitative approach to data analysis, whereby the corpus data were analysed using a lexical analysis software AntWordProfiler and descriptive statistics were applied to obtain the frequency and percentage of the results. The corpus data, which were the compilation of the writings from 241 first semester students, stood at 106, 015-word tokens. The findings reveal an overall high (87%) GSL1 level and low GSL2 and AWL (5% and 2% respectively) in the student writings, while there is also almost no difference in results between disciplines in GSL1, GSL2 and AWL levels. The study concludes that the participants in general have insubstantial lexical knowledge that may affect their ability to function independently in the academic setting.